Lidar stand-alone retrieval of atmospheric aerosol microphysical properties during SLOPE - Ortiz-Amezcua Pablo; Samaras Stefanos; Böckmann Christine; Antonio Benavent-Oltra Jose; Luis Guerrero-Rascado Juan; Román Roberto; Alados-Arboledas Lucas (EPJ Web of Conferences, 2018)
Two cases from SLOPE campaign at Granada are analyzed in terms of particle microphysical properties using novel software developed at Potsdam University. Multiwavelength Raman lidar measurements of particle extinction and backscatter coefficients as well as linear particle depolarization ratios are used as input for the software. The result of the retrieval is a 2-dimensional particle volume distribution as a function of radius and aspect ratio, from which the particle microphysical properties are obtained.